External Finance for Private Sector Development Appraisals and Issues - Odedokun, Matthew (Palgrave Macmillan UK, 2004)
Foreign finance for private sector development (PSD) has become popular with the donor community and in multilateral development policy fora, seen as an antidote for recipient economies' aid dependency and a way of accomplishing growth, poverty reduction and empowerment. This book analyzes the pattern of foreign finance for PSD and examines multilateral and bilateral donors' practices in PSD financing, giving special attention to microfinance and microenterprises. It also models and explains private capital flows from developed to developing countries and reverse flows in the form of capital flight